Rhizobial plasmid pLPU83a is able to switch between different transfer machineries depending on its genomic background - Torres Tejerizo, Gonzalo Arturo (2014)
Plasmids have played a major role in bacterial evolution, mainly by their capacity to perform horizontal gene transfer (HGT). Their conjugative transfer (CT) properties are usually described in terms of the plasmid itself. In this work, we analyzed structural and functional aspects of the CT of pLPU83a, an accessory replicon from Rhizobium sp. LPU83, able to transfer from its parental strain, from Ensifer meliloti, or from Rhizobium etli. pLPU83a contains a complete set of transfer genes, featuring a particular organization, shared with only two other rhizobial plasmids. These plasmids contain a TraR quorum-sensing (QS) transcriptional regulator, but lack an acyl-homoserine lactone (AHL) synthase gene. We also determined that the ability of pLPU83a to transfer from R. etli CFN42 genomic background was mainly achieved through mobilization, employing the machinery of the endogenous plasmid pRetCFN42a, falling under control of the QS regulators from pRetCFN42a. In contrast, from its native or from the E. meliloti background, pLPU83a utilized its own machinery for conjugation, requiring the plasmid-encoded traR. Activation of TraR seemed to be AHL independent. The results obtained indicate that the CT phenotype of a plasmid is dictated not only by the genes it carries, but by their interaction with its genomic context.